Typology of informal learning spaces (ILS) in sustainable academic education: a systematic literature review in Architecture and Urban Planning - Salih, Sarah Abdulkareem; Alzamil, Waleed; Ajlan, Ali; Azmi, Athira; Ismail, Sumarni (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Informal learning spaces (ILS) offer unique opportunities for students to interact and develop skills in a more social, resilient, and sustainable environment. However, there is a lack of a definitive typology for ILS and related design factors and outcomes. Therefore, this study aimed to identify the typology of ILS in academic education, including relevant design factors and positive outcomes from architectural and urban planning perspectives. A systematic literature review was conducted on articles published between 2004 and 2024 from four databases: Scopus, ScienceDirect, Emerald Insights, and IEEE Xplore. The included articles are in English and based on empirical data published in peer-reviewed journals, focusing on informal learning and its settings. A total of 37 full-text articles were included in the descriptive review, from which two categories and six types were identified: private indoor quiet space, semi-private/semi-public indoor space, public indoor space, public sustainable space, public outdoor space, and comprehensive space. The results also revealed seven categories of factors affecting these types of ILS: personal aspects, spatial design, physical settings, resources, social aspects, natural environment, and perceived environment. Furthermore, these ILS significantly contributed to five categories of positive outcomes: learning efficacy, socialisation, refreshment and relaxation, health outcomes, and sustainable development. Therefore, this SLR significantly contributed to the definition and typology of ILS in sustainable higher education.